2019
DOI: 10.1002/ccr3.2455
|View full text |Cite
|
Sign up to set email alerts
|

A congenital cystic pulmonary airway malformation occurring together with both an extralobar pulmonary sequestration and an esophageal duplication cyst

Abstract: A foregut duplication cyst occurring together with both a congenital cystic pulmonary airway malformation and extralobar pulmonary sequestration is an unusual combination. Prenatal ultrasound, MRI, and postnatal CT are helpful for operative planning. Surgical resection is the definitive management for all three anomalies. K E Y W O R D Scystic lung disease, cystic pulmonary airway malformation, esophageal duplication cyst, extralobar pulmonary sequestration, prenatal imaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…ELS is almost discovered on regular antenatal ultrasonographic screening or incidentally detected in later life. A few of ELS are identified accompanied with other congenital anomalies, such as congenital diaphragmatic hernia (CDH) or diaphragmatic eventration, cardiac defects, foregut anomalies, and congenital pulmonary airway malformation (CPAM) 11–14 . The previous study demonstrated that ELS patients might remain asymptomatic throughout life without any surgical intervention 1 .…”
Section: Introductionmentioning
confidence: 99%
“…ELS is almost discovered on regular antenatal ultrasonographic screening or incidentally detected in later life. A few of ELS are identified accompanied with other congenital anomalies, such as congenital diaphragmatic hernia (CDH) or diaphragmatic eventration, cardiac defects, foregut anomalies, and congenital pulmonary airway malformation (CPAM) 11–14 . The previous study demonstrated that ELS patients might remain asymptomatic throughout life without any surgical intervention 1 .…”
Section: Introductionmentioning
confidence: 99%